Development of the optimal composition of tablets with the active substance potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate. Message 1. Study of the effect of auxiliary substances on bulk density, bulk density after shrinkage, fluidity and angle of natural slope of powder masses - R. O. Shcherbyna; O. V. Khromylova; H. R. Nimenko; V. O. Salionov (Zaporozhye State Medical University, 2024)
The pharmaceutical industry continually evolves to meet the demands of modern society for high-quality medications. One avenue of this advancement involves exploring new technologies for manufacturing tablet formulations that adhere to contemporary quality standards. An integral aspect of this process is the careful selection of optimal excipients that preserve the pharmacological activity of the active substance to the greatest extent possible. Investigating the impact of various excipients on the tablet compression process is pivotal to addressing this challenge. Therefore, the study of the influence of excipients on the pharmaco-technological properties of tablets with potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate is an important aspect, so as this substance has pronounced hepatoprotective and antioxidant properties. The aim of the work was to study the effect of excipients on the pharmaco-technological parameters of tablets with the active ingredient potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate obtained by the method direct pressing. Materials and methods. Active substance - potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate, auxiliary substances (excipients based on microcrystalline cellulose, auxiliary substances based on granulated sugars, lubricants, lubricants). The powder mixtures were checked for bulk density, bulk density after compaction, flowability and angle of natural slope. The tablets were pressed by the direct pressing method. The effect of auxiliary substances on the pressing process was studied. Results. The conducted studies show that the powder mass of potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazol-3-yl)thio)acetate and auxiliary substances was characterized by good pharmaco-technological indicators - bulk density and bulk density after compaction, fluidity and angle of natural slope. Further, during the tableting process, it was confirmed that the powder mass has satisfactory properties. In almost all series of experiments, the process of pressing the tablets took place without difficulties, the matrix was evenly filled, but the force of pushing the tablets out of the matrix was different. Conclusions. The study involving 16 excipients, including fillers, disintegrants, and lubricants to develop the composition and technology was conducted of a new tablet medicine containing potassium 2-((4-amino-5-(morpholinomethyl)-4H-1,2,4-triazole-3-yl)thio)acetate. This comprehensive examination enabled us to identify the optimal auxiliary substances that fulfill all the pharmaco-technological requirements stipulated by the State Pharmacopoeia of Ukraine for tablet formulations.